Menggugat Islam Indonesia Dalam Mewujudkan Religious Peacebuilding Di Era Konflik: Challenging Indonesian Islam in Realizing Religious Peacebuilding in the Era of Conflict - Asy'ari Asy'ari (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2017)
Plurality in Indonesia has the potential to generate both harmony and multidimensional conflict, including religiously charged violence that emerged after the reform era. This article aims to challenge the position of Indonesian Islam as the majority religion in realizing religious peacebuilding amid an era of conflict. Through a qualitative library research approach, the author analyzes various communal conflict phenomena such as the Situbondo, Tasikmalaya, and Ambon riots, while exploring the concepts of dialogue, peace education, and Djohan Effendi’s secularism as resolution strategies. The main findings indicate that Indonesian Islam holds great potential as a source of peace, but religious symbols are often used to justify violence due to absolutism, fanaticism, and exclusivism. In conclusion, a peace militancy from religious leaders, implementation of empathetic interreligious dialogue, and an inclusive educational curriculum from an early age are required to transform the culture of violence into a culture of peace. The recommendation is that religious and political actors must integrate universal religious values such as justice and humanity into every concrete action of conflict prevention. Pluralitas di Indonesia berpotensi melahirkan harmoni sekaligus konflik multidimensional, termasuk kekerasan bernuansa agama yang muncul pasca reformasi. Artikel ini bertujuan menggugat posisi Islam Indonesia sebagai agama mayoritas dalam mewujudkan religious peacebuilding di tengah era konflik. Melalui pendekatan kualitatif berbasis kajian pustaka, penulis menganalisis berbagai fenomena konflik komunal seperti kerusuhan Situbondo, Tasikmalaya, dan Ambon, serta mengeksplorasi konsep dialog, pendidikan perdamaian, dan sekularisme ala Djohan Effendi sebagai strategi resolusi. Temuan utama menunjukkan bahwa Islam Indonesia memiliki potensi besar sebagai sumber perdamaian, namun seringkali simbol-simbol agama dimanfaatkan untuk membenarkan kekerasan akibat sikap absolutisme, fanatisme, dan eksklusivisme. Kesimpulannya, diperlukan militansi perdamaian dari para agamawan, implementasi dialog antaragama yang empatik, serta kurikulum pendidikan inklusif sejak dini untuk mentransformasi budaya kekerasan menuju budaya damai. Rekomendasinya, aktor agama dan politik harus mengintegrasikan nilai-nilai universal agama seperti keadilan dan kemanusiaan dalam setiap aksi konkret pencegahan konflik.